Blue Innovation, Value Creation, and Decision-making on Digital Performance and Sustainability - Renaldo, Nicholas; Junaedi, Achmad Tavip; Suhardjo, Suhardjo; Veronica, Kristy; Augustine, Yvonne; Musa, Sulaiman; Cecilia, Cecilia (Journal of Applied Business and Technology, 2024)
This study proposed model framework introduces a novel approach by positioning Blue Innovation as a primary driver of Value Creation and Decision-Making, which in turn mediate the relationship between Digital Performance and Sustainability. In this quantitative research, data will be collected using a structured questionnaire. The sample size will be 155 respondents. This study uses Structural Equation Modeling (SEM) analysis to analyze the influence of independent, intervening, and control variables on the dependent variable. The findings provide significant insights into how these variables interact and influence one another, summarized as blue innovation significantly enhances digital performance, value creation has a strong positive impact on digital performance, decision-making significantly improves digital performance, blue innovation positively influences sustainability, value creation cannot directly increase sustainability, decision-making has a significant positive impact on sustainability, digital performance significantly enhances sustainability, blue innovation increases sustainability through digital performance, value creation indirectly increases sustainability through digital performance, decision-making positively influences sustainability through digital performance.